Mercury in the Arctic - AMAP, -
The Arctic Monitoring and Assessment Programme (AMAP) recently published a detailed scientific assessment on mercury in the Arctic, updating previous assessments made in 1998 and 2004. Main questions addressed in this latest assessment were: Where does mercury in the Arctic environment come from, and how does it get there? and What controls mercury levels in the Arctic and what are the effects on Arctic biota, including Arctic human populations?